CONODONT BIOSTRATIGRAPHY AND LITHOSTRATIGRAPHY ACROSS THE PERMIAN-TRIASSIC BOUNDARY AT THE LUKAC SECTION IN WESTERN SLOVENIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Detailed conodont biostratigraphy and lithostratigraphy of the Late Permian and Early Triassic beds were studied at the LukaC section in western Slovenia. The analyzed section is composed of the Bellerophon Formation ("evaporite-dolomite member") and the newly introduced Lukaè Formation ("transitional beds", "streaky limestone member" and "carbonate-clastic beds member"). The Permian-Triassic boundary interval is represented by "transitional beds" of carbonate facies deposited in shallow restricted marine conditions. The presence of H. parvus in sample L1 in the "transitional beds" marks the systemic boundary between Permian and Triassic. The studied interval is characterized by a diverse microfauna that contain conodonts, foraminifers, ostracods and gastropods. Six conodont zones have been recognized, in ascending order, the latest Changhsingian (uppermost Permian) praeparvus Zone, and the Griesbachian (lowermost Triassic) parvus, lobata, staeschei-isarcica, postparvus and anceps zones. This faunal succession represents the first known and the most complete conodont biozonation across the Permian-Triassic interval from the entire Dinaric region. The recognized conodont biozones can be correlated with the biozonation of the Southern Alps and of the GSSP Meishan D section.
Keywords: Conodont biostratigraphy; Permian-Triassic boundary; Dinarides; Slovenia